(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article analyzes the role of obstetric care in protecting the health of women of reproductive age on the basis of international experimental and scientific sources. Relying on who and ICM data, qualified obstetric care is based on a significant (16-33%) reduction in maternal and child mortality. The article highlights the effectiveness of the woman-oriented continuous care model, as well as the fact that the working conditions and professional satisfaction of medical workers are a factor that directly affects the safety of patients. An analysis of the experience of Germany and other European countries is cited as a theoretical basis for the reform of the health system of Uzbekistan.